Дослідження кредитних ризиків комерційних банків та методи їх оцінювання - Віблий, П. І.; Жарчинська, А. Ю.; Viblyi, P. I.; Zharchynska, A. Y. (Видавництво Львівської політехніки, 2019)
Досліджено кредитні ризики комерційних банків та методи їх оцінювання, необхідність аналізування кредитних ризиків банківськими установами. Вивчено найефективніші моделі оцінювання кредитного ризику. На основі – моделі Альтмана було оцінено українські підприємства щодо кредитоспроможності та банкрутства, також проаналізовано структурну модель Мертона.

The article analyzes the credit risks of commercial banks and methods of their evaluation. Investigated the necessity of carrying out analysis of credit risks by banking institutions. The most effective models for assessing credit risk were studied. On the basis of the -model of Altman, Ukrainian companies were assessed for credit and bankruptcy, and Murton’s structural model was analyzed. The purpose of the work is to investigate methods of assessing credit risks of commercial banks based on leading models of bank risk assessment, as well as justification of the necessity of using these methods for all credit institutions. It has been proven that, in accordance with the Basel Accord, known as Basel II, in order to assess borrowers during lending, it is recommended to apply an approach based on credit ratings created within a credit institution. This approach involves developing the structure of the rating system, which includes individual assessment of borrowers’ credit risk and their distribution by rating system grades, as well as a quantitative estimate of default risk, probability of survival and actually incurred losses. Implementation of all methods directly determines the efficiency of management of credit risk. Creating ways to manage credit risk includes methods for reducing the level of risk. Also, the most effective models of credit risk assessment were identified, among which: 1. Expert analysis of the borrower. It is this type of analysis that is traditionally used in assessing the solvency of a bank customer. 2. Regression models and scoring. The main idea of a credit scoring is that each borrower is assigned a real credit risk assessment and an assessment of the probability of default, indicating that such a scoring assessment of borrowers is an indicator of risk. It was also investigated which of the proposed Ukrainian borrowers would be the most credible, and the most profitable and reliable customer for a commercial bank. Using Altman Z-score it was calculated creditworthiness of such enterprises for the last period as: PJSC “Ukrnafta”, PJSC “Halychfarm”, PJSC “Kyiv confectionery factory Roshen”. These enterprises are leaders in their fields. From this comparison, it was determined that the most profitable for the Ukrainian business is the pharmaceutical industry. It is concluded that PJSC “Halychfarm” will be the most reliable and stable borrower for a credit institution, in our case for commercial banks, such an enterprise will be interesting for investors as well. Murton’s structural model was also analyzed. It has been proven that relying only on credit risk assessment using leading models can increase the profitability of a lending institution and reduce the possibility of losses by providing lending to trusted vendors that are creditworthy.
Credit risk analysis of commercial banks and methods of their assessment
Keywords: банківський ризик; кредитний ризик; дефолт; регулювання кредитного ризику; bank risk; credit risk; default; credit risk regulation; 330.4; 336.71